2014
DOI: 10.1186/s12931-014-0122-1
|View full text |Cite
|
Sign up to set email alerts
|

Observational study to characterise 24-hour COPD symptoms and their relationship with patient-reported outcomes: results from the ASSESS study

Abstract: BackgroundFew studies have investigated the 24-hour symptom profile in patients with COPD or how symptoms during the 24-hour day are inter-related. This observational study assessed the prevalence, severity and relationship between night-time, early morning and daytime COPD symptoms and explored the relationship between 24-hour symptoms and other patient-reported outcomes.MethodsThe study enrolled patients with stable COPD in clinical practice. Baseline night-time, early morning and daytime symptoms (symptom q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(107 citation statements)
references
References 33 publications
6
87
1
13
Order By: Relevance
“…Chronic and progressive dyspnoea is the cardinal symptom of COPD and a major cause of disability in these patients. 8 A simple measure of dyspnoea is the Modified British Medical Research Council (mMRC) Questionaire. 9 The mMRC questionnaire relates well to other measures of health status and predicts future mortality risk.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic and progressive dyspnoea is the cardinal symptom of COPD and a major cause of disability in these patients. 8 A simple measure of dyspnoea is the Modified British Medical Research Council (mMRC) Questionaire. 9 The mMRC questionnaire relates well to other measures of health status and predicts future mortality risk.…”
Section: Introductionmentioning
confidence: 99%
“…The recent observational ASSESS study, which included more than 700 patients with COPD, performed in a real-life context, has confirmed the significant prevalence of nighttime symptoms (52%), which tend to be associated both with greater symptom severity, as assessed by the COPD Assessment Test (CAT), and higher prevalence of anxiety and depression, as assessed by the Hospital Anxiety and Depression Scale (HADS) [16]. In the clinical practice, however, the circadian variability is often not adequately taken into consideration in the therapeutic approach; for example, a real-life clinical study showed that drug treatment was not changed in more than half of patients surveyed, even though a significant worsening of symptoms over 24 h was noted.…”
Section: Main Textmentioning
confidence: 97%
“…The PKs of GFF MDI support twice-daily administration and the improvements in lung function demonstrated here after BID dosing with GFF MDI as maintenance dual-bronchodilator therapy may provide benefits over QD dosing, preventing excessive worsening of symptoms during the night or towards the morning in patients with this pattern of symptoms [7]. The results of a patient evaluation survey conducted by Partridge et al, and similarly in the ASSESS study, show that patients with COPD begin to experience worsening symptoms in the evening through the night-time, with the worst symptoms, affecting activity and productivity, occurring in the morning [22, 23]. This is also an area for future investigation of the effects of GFF MDI on COPD symptom burden.…”
Section: Discussionmentioning
confidence: 99%